Creep and Hygrothermal Effects in Concrete Structures - Bažant, Zdeněk P.; Jirásek, Milan; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2018)
This comprehensive treatise covers in detail practical methods of analysis as well as advanced mathematical models for structures highly sensitive to creep and shrinkage. Effective computational algorithms for century-long creep effects in structures, moisture diffusion and high temperature effects are presented. The main design codes and recommendations (including RILEM B3 and B4) are critically compared. Statistical uncertainty of century-long predictions is analyzed and its reduction by extrapolation is discussed, with emphasis on updating based on short-time tests and on long-term measurements on existing structures. Testing methods and the statistics of large randomly collected databases are critically appraised and improvements of predictions of multi-decade relaxation of prestressing steel, cyclic creep in bridges, cracking damage, etc., are demonstrated. Important research directions, such as nanomechanical and probabilistic modeling, are identified, and the need for separating the long-lasting autogenous shrinkage of modern concretes from the creep and drying shrinkage data and introducing it into practical prediction models is emphasized. All the results are derived mathematically and justified as much as possible by extensive test data. The theoretical background in linear viscoelasticity with aging is covered in detail. The didactic style makes the book suitable as a textbook. Everything is properly explained, step by step, with a wealth of application examples as well as simple illustrations of the basic phenomena which could alternate as homeworks or exams. The book is of interest to practicing engineers, researchers, educators and graduate students.
Part I Fundamentals -- 1 Introduction -- 2 Fundamentals of Linear Viscoelasticity -- 3 Basic Properties of Concrete Creep, Shrinkage and Drying -- 4 Structural Effects of Creep and AAEM -- 5 Numerical Analysis of Creep Problems -- 6 Uncertainty Due to Parameter Randomness -- 7 Paradigms of Application, Phenomena Affecting Creep -- Part II Advanced Topics -- 8 Moisture Transport in Concrete -- 9 Solidification Theory -- 10 Microprestress-Solidification Theory -- 11 Physical and Statistical Justifications of Models B3 and B4 -- 12 Cracking and Fracture Mechanics Aspects -- 13 Temperature Effect -- A Viscoelastic Rheologic Models -- B Historical Note on Old Creep Models -- C Estimates of Parameters Used By RILEM Model B3 -- D Estimates of Parameters Used By RILEM Model B4 -- ECreep Models Recommended by Design Codes -- F Continuous Retardation Spectrum -- G Updating Long-Time Shrinkage Predictions -- H Transport Properties -- I Moisture Transport in Porous Materials -- J Nonstandard Statistics -- K Potentials for Aging Viscoelasticity -- L Method of Measurement of Creep and Shrinkage.
Keywords: Building materials; Mechanics, Applied; Solids; Structural Materials; Solid Mechanics